CONSTRUCTING HOM-(TRI)DENDRIFORM FAMILY ALGEBRAS - ATTAN, SYLVAIN; Gaparayi, Donatien; KPAMEGAN, ASSOGBA BERNARDIN (My University, 2022)
Hom-(tri)dendriform family algebras and Hom-pre-Lie family al- gebras are introduced and studied. Moreover we explore the connections be- tween these categories of family Hom-algebras.
Keywords: Hom-associative algebras; Rota-Baxter family; Hom-dendriform fam-; ily algebras; Hom-tridendriform family algebras; Hom-pre-Lie family algebras.